Sensory Evaluation of Milkfish Pempek with the Addition of Shrimp Flour for Food Product Diversification in Indonesia - Amelia Dwi Nugrahaini; Julia Agustina; Rahmat Dhandy; Elis Rahmawati Mar’atus Sholihah; Andi Muhammad Ismail; Muhammad Al Fathir; Cantika Putri Hapsari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study aimed to evaluate the effect of shrimp by-product flour fortification on consumer acceptance of milkfish (Chanos chanos) pempek. Three treatments were tested: Pempek A (0% shrimp by-product flour), Pempek B (10%), and Pempek C (15%). A total of 40 untrained panelists assessed the sensory attributes using a 5-point hedonic scale, including taste, aroma, texture, color, aftertaste, and the feasibility of routine consumption. Data were analyzed using Analysis of Variance (ANOVA) followed by Tukey's HSD test at a 5% significance level (α = 0.05) using SPSS version 25. The results showed significant differences (p<0.05) in taste, color, and aftertaste among treatments, whereas aroma, texture, and the feasibility of routine consumption did not differ significantly (p>0.05). Pempek B (10%) obtained the highest taste score = 3.95 ± 0.12, followed by Pempek A (3.88 ± 0.15) and Pempek C (3.52 ± 0.18). The 15% fortification tended to decrease consumer preference due to a darker appearance and more pungent shrimp aftertaste, while 10% fortification was still well-accepted without reducing sensory quality. Therefore, fortification at the 10% level is considered the most optimal formulation, producing a milkfish pempek with favorable sensory properties while supporting the sustainable utilization of fishery by-products. This study contributes to the sustainable utilization of shrimp by-products in local food diversification through consumer-oriented product innovation.